Hybrid electric vehicle system modeling and control - Liu, Wei, 1960 August 30- (Automotive series (Wiley), 2017)
Intended to contribute to a better understanding of hybrid electric vehicle systems, this thorough reference presents all the major aspects of hybrid vehicle modeling, control, simulation, performance analysis, and preliminary design. --